(untitled) (ETIMA, 2024)
The aim of the expertise in this case study was to find out the cause of the malfunctioning of the lamps in the production hall. The light source was a halogen discharge lamp with a nominal power of 400 W. In accordance with the requirements of the investor, the lighting intensity regulation was installed in the premises of the production hall according to the daily light conditions. In conclusion, we explain the physical and chemical mechanism of the cause of failures of a halogen lamp with a nominal power of 400 W. Due to uncontrollable nonequilibrium states and changes in activation energy, the regulation of the discharge of halogen lamps with a nominal power of 400 W is inappropriate.